Digital smile design and 3D digital wax-up approaches for zirconia long-span bridge: Digital smile design dan pendekatan digital wax-up digital 3D untuk long-span bridge zirkonia - Miftahendarwati; Mude, Acing Habibie; Launardo, Vinsensia; Polanunu, Siti Magfira Ali; Jubhari, Eri Hendra (Makassar Dental Journal PDGI Makassar, 2025)
Dental agenesis is the most common congenital abnormality that occurs in permanent teeth. Digital smile design (DSD) is a technology that digitally designs and modifies a patient's smile by creating a digital wax-up (DWU) before treatment begins. This aids visual communication and patient involvement in their own smile design process, thus ensuring predictable treatment out-comes and increasing patient acceptance. This article reports on maxillary anterior rehabilitation with zirconia long-span bridge illustrating aesthetic planning with DSD system and 3D DWU technique. A 21-year-old male came to the Department of Prostho-dontia, Hasanuddin University with complaints of a half-crown fracture of tooth 11 and missing teeth 12, 21, and 22. Radiographs of teeth 12 and 22 were agenesis because there were no seeds and had never been extracted so the smile was not aesthetic. Root canal treatment had previously been performed on teeth 11 and 13 with fibre post. It was concluded that the use of DSD and 3D DWU for the treatment of zirconia long-span bridge is a rehabilitation treatment option for upper edentulous parsialis. This prosthesis improved facial and dental aesthetics, functional occlusion, phonetics, and comfort.